2002
DOI: 10.1159/000049269
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Facial Nerve Palsy following Uneventful Stapedectomy

Abstract: Facial nerve palsy is a rare complication of stapedectomy. Its onset may be immediate or delayed by several days. The authors present a case of a 59-year-old man who developed right delayed peripheral facial nerve palsy occurring after uncomplicated ipsilateral stapedectomy. The incidence, treatment and prognosis of this complication are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Among the various complications, facial palsy, or weakness is the most concerning. Some studies reported incidence rates ranging from 0.07% to 1%, 18 whereas another publication cited an incidence rate of 0.51%. 9 Although none of the cases included herein developed total facial palsy, two patients (1.88%) experienced grade II facial weakness following surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Among the various complications, facial palsy, or weakness is the most concerning. Some studies reported incidence rates ranging from 0.07% to 1%, 18 whereas another publication cited an incidence rate of 0.51%. 9 Although none of the cases included herein developed total facial palsy, two patients (1.88%) experienced grade II facial weakness following surgery.…”
Section: Discussionmentioning
confidence: 99%